2019
DOI: 10.1111/ina.12543
|View full text |Cite
|
Sign up to set email alerts
|

Effective disinfection of airborne microbial contamination in hospital wards using a zero‐valent nano‐silver/TiO 2 ‐chitosan composite

Abstract: A novel antimicrobial composite of zero‐valent silver nanoparticles (AgNPs), titania (TiO2), and chitosan (CS) was prepared via photochemical deposition of AgNPs on a CS‐TiO2 matrix (AgNPs@CS‐TiO2). Electron microscopy showed that the AgNPs were well dispersed on the CS‐TiO2, with diameters of 6.69‐8.84 nm. X‐ray photoelectron spectra indicated that most of the AgNPs were reduced to metallic Ag. Fourier‐transform infrared spectroscopy indicated that some AgNPs formed a chelate with CS through coordination of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…The contribution of airborne microorganisms to food contamination has been addressed (Chang, et al, 2019;Chen et al, 2019;Shale & Lues, 2007). Burfoot and Brown (2004) reported that the ratio of microorganisms to total particles may range up to more than two orders of magnitude.…”
Section: What Is a Bioaerosol And Why Air Monitoring Is Important?mentioning
confidence: 99%
See 1 more Smart Citation
“…The contribution of airborne microorganisms to food contamination has been addressed (Chang, et al, 2019;Chen et al, 2019;Shale & Lues, 2007). Burfoot and Brown (2004) reported that the ratio of microorganisms to total particles may range up to more than two orders of magnitude.…”
Section: What Is a Bioaerosol And Why Air Monitoring Is Important?mentioning
confidence: 99%
“…-++, frequent use; +, occasional use; -, not used. Sources: Burfoot, Hall, Brown, & Xu, 1999;Marriott & Gravani, 2006;Pascual, Llorca, & Canut, 2007;Stanga, 2010;Krishnan et al, 2012;Cutler & Zimmerman, 2011;O'Donnell, Tiwari, Cullen, & Rice, 2012;Christ, Savi, & Scussel, 2016;Zhou, Yang, Lai, & Huang, 2016;Yang, Zhang, Nunayon, Chan, & Lai, 2018;Chen et al, 2019;Masotti et al, 2019.…”
mentioning
confidence: 99%
“…The titania-chitosan (TiO 2 -CS) composite was prepared according to our previously reported method. (19) Briefly, 15 g of chitosan was completely dissolved in acetic acid solution (600 mL, 3% v/v, pH = 2.6). Then, 2.4 g of P25 TiO 2 powder (particle size 25-30 nm; Brunauer-Emmett-Teller [BET] surface area 53.3 m 2 /g; 80% in the anatase phase and 20% in the rutile phase) was added to the viscous chitosan solution, and then the slurry was nonstop stirred for 24 hours to obtain a viscous colloid.…”
Section: Preparation and Characterization Of The Nano-ag 0 /Tio 2 -Cs Compositementioning
confidence: 99%
“…(18) Our previous study has demonstrated the excellent bactericidal efficacy of zero-valent nanosilver/titania-chitosan (nano-Ag 0 /TiO 2 -CS) composite for purifying the supply air in hospital wards. (19) However, due to the different structures and aerosol particle sizes between viruses and bacteria, (20)(21)(22)(23) the antimicrobial efficacy of nano-Ag 0 /TiO 2 -CS against viruses and bacteria would also be different. Thus, the primary aim of this study is to evaluate the filtration efficiency and antiviral efficacy of nano-Ag 0 /TiO 2 -CS filter for viral aerosols, along with the assessment of the infection risk reduction and longterm antiviral efficacy of nano-Ag 0 /TiO 2 -CS.…”
Section: Introductionmentioning
confidence: 99%
“…Ozden and Basal (2017) applied polyamide 6/chitosan nanofiber-coated on HEPA filter for controlling bioaerosols [19]. Chen et al (2019) used zero-valent nano-silver/Ti0 2 -chitosan composite filters to remove hospital indoor bioaerosols [20]. Mishra et al (2021) applied lemongrass essential oil loaded on chitosan nanocellulose for inactivating bioaerosols [21].…”
Section: Introductionmentioning
confidence: 99%